2010
DOI: 10.4049/jimmunol.0901115
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-Induced Th17 Responses Modulate Th1 Cell Responses, Benefit Bacterial Growth, and Contribute to Pathology in Mice

Abstract: CD4+ T cell responses are critical for the pathogenesis of Helicobacter pylori infection. The present study evaluated the role of the Th17 subset in H. pylori infection. H. pylori infection induced significant expression of IL-17 and IFN-g in mouse gastric tissue. IL-23 and IL-12 were increased in the gastric tissue and in H. pylori-stimulated macrophages. Cell responses were examined by intracellular staining for IFN-g, IL-4, and IL-17. Mice infected with H. pylori developed a mixed Th17/Th1 response; Th17 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
164
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(178 citation statements)
references
References 39 publications
10
164
2
2
Order By: Relevance
“…3C). This finding is consistent with previous evidence showing IL-17 expression in H. pylori-infected gastric tissue (9,12,17). Furthermore, studies have shown that depletion of IL-17 or the use of IL-17 −/− mice lowers both H. pylori colonization levels and inflammation grade (12).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…3C). This finding is consistent with previous evidence showing IL-17 expression in H. pylori-infected gastric tissue (9,12,17). Furthermore, studies have shown that depletion of IL-17 or the use of IL-17 −/− mice lowers both H. pylori colonization levels and inflammation grade (12).…”
Section: Resultssupporting
confidence: 83%
“…However, the roles of the Th17 and T-reg cell populations during H. pylori infections have been debated recently. The Th17 cell is involved in promoting chronic inflammation (11,12); the Treg cell, in contrast, regulates host immune responses. Th17 and Treg cells are developmentally related and exist in a delicate balance (13) that can dictate the outcome of a bacterial infection (14).…”
mentioning
confidence: 99%
“…Many data support the idea that the Th17 response favors the bacterial growth in mice and contributes to the inflammation both in mice and in humans (3)(4)(5), although its role is probably not essential because IFN-g has the largest effect (2). Along with this evidence, other data suggest that this response may exert a regulatory effect rather than a proinflammatory one (6).…”
mentioning
confidence: 62%
“…The infiltration of Th17 cells in the gastric mucosa of H. pyloriinfected patients is well established (3,21). To confirm this evidence, we evaluated the expression of IL-17, in terms of both mRNA and protein, in the mucosa of H. pylori-infected patients with nonatrophic chronic gastritis, a condition that represents a risk for the development of more severe gastric diseases (22).…”
Section: Il-17 and Baff Are Increased In H Pylori-induced Chronic Gamentioning
confidence: 99%
See 1 more Smart Citation